2009
DOI: 10.1159/000224336
|View full text |Cite
|
Sign up to set email alerts
|

Birth Size, Postnatal Growth and Growth during Growth Hormone Treatment in Small-for-Gestational-Age Children: Associations with <i>IGF1</i> Gene Polymorphisms and Haplotypes?

Abstract: Background: Short small-for-gestational-age (SGA) children experience pre- and postnatal growth restriction, which might be influenced by polymorphisms in the IGF1 gene. The well-known –841(CA)n/192 bp polymorphism has been associated with birth size and cardiovascular disease. Aims: To determine whether birth size, postnatal growth and growth during growth hormone (GH) treatment, were associated with IGF1 gene polymorphisms and haplotypes. Methods: 201 short SGA children were investigated for four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 94 publications
2
10
0
Order By: Relevance
“…Our findings suggest that the genetic factors that determine permanent short stature in children born SGA are mainly of paternal origin; this phenomenon has been previously described in the literature (46). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings suggest that the genetic factors that determine permanent short stature in children born SGA are mainly of paternal origin; this phenomenon has been previously described in the literature (46). …”
Section: Discussionsupporting
confidence: 80%
“…In another study, four IGF1 gene polymorphisms were analyzed in 201 short-SGA children (46), and no association of CA repeats with birth size or postnatal growth was observed (Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…The Swedish Study Group for Growth Hormone Treatment shows better catch-up growth in shorter and younger SGA children [45], although the absence of association between gestational age-adjusted birth size, height, and weight standard deviation score (SDS) and growth during GH treatment has been reported [46]. Recently, Ester et al have shown that the −G1245A single nucleotide polymorphism in the IGF-I gene appears to be a marker for the well known −841(CA) n /192 bp polymorphism [46].…”
Section: Growth Hormone Therapymentioning
confidence: 99%
“…Recently, Ester et al have shown that the −G1245A single nucleotide polymorphism in the IGF-I gene appears to be a marker for the well known −841(CA) n /192 bp polymorphism [46]. Furthermore, a polymorphic variation in the IGFBP-3 promoter region has been correlated with IGFBP-3 levels, spontaneous growth, and response to GH treatment in children born SGA [47].…”
Section: Growth Hormone Therapymentioning
confidence: 99%
“…Twin studies have shown that 40-65% of interindividual variability in IGF-I, IGF-II and IGFBP-3 levels is genetically determined (Harrela et al, 1996). Single nucleotide polymorphisms in the IGF-I gene are correlated with IGF-I levels, head circumference in short SGA children, birth weight and increased risk of type 2 diabetes and ischemic heart disease, although not all studies found similar associations (Ester et al, 2009b;Frayling et al, 2002;Johnston et al, 2003;Vaessen et al, 2001). …”
Section: Igf and Igf Receptor Genesmentioning
confidence: 99%